1994
DOI: 10.1677/joe.0.1400425
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose cortisol infusion increases plasma corticosteroid-binding globulin (CBG) and the amount of hepatic CBG mRNA in fetal sheep on day 100 of gestation

Abstract: Synthetic glucocorticoids stimulate the production of corticosteroid-binding globulin (CBG) by the liver of the sheep fetus near term (day 145). We have examined whether physiological changes in plasma cortisol alter plasma CBG concentrations, patterns of glycosylation and the amount of hepatic CBG mRNA at earlier times during pregnancy (day 100), prior to the activation of fetal hypothalamic-pituitary-adrenal function. Cortisol was infused into chronically catheterized sheep fetuses in amounts that raised the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…It has been suggested previously that an increase in fetal plasma CBG late in gestation maintains low concentrations of circulating cortisol and therefore maintains low negative feedback on the pituitary and the hypothalamus (Ballard et al 1982, Berdusco et al 1994. Glucocorticoids have been shown to increase plasma CBC and hepatic CBG mRNA in fetal sheep (Berdusco et al 1994).…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested previously that an increase in fetal plasma CBG late in gestation maintains low concentrations of circulating cortisol and therefore maintains low negative feedback on the pituitary and the hypothalamus (Ballard et al 1982, Berdusco et al 1994. Glucocorticoids have been shown to increase plasma CBC and hepatic CBG mRNA in fetal sheep (Berdusco et al 1994).…”
Section: Discussionmentioning
confidence: 97%
“…molecular cloning of a part of the promoter of the human CBG gene [30] failed to evidence consensus sites for steroid receptors. However, physiological changes in plasma cortisol due to infusion of this hormone increased significantly CBG mRNA in the fetal sheep liv er and the corresponding corticosteroid-binding capacity in the plasma [31]. This was even prior to the activation by glucocorticoids of the fetal hypothalamic-pituitaryadrenal axis, that play a crucial role for delivery in this species.…”
Section: Regulation Factorsmentioning
confidence: 93%
“…The major site of CBG production is the liver, where CBG mRNA levels increase with advancing gestational age (110). Cortisol increases hepatic CBG mRNA, thus providing a mechanism whereby cortisol itself may maintain low free cortisol concentrations in the fetal circulation (121,122). Using pituitary cells in culture is has been shown that CBG attenuates the negative feedback effects of cortisol on ACTH secretion, thus indicating a physio卢 logical role for systemic CBG in modulating cortisol feedback efficacy at the level of the pituitary gland (119).…”
Section: Hypothalamic Drivementioning
confidence: 99%
“…Effect of intravenous administration of saline (O) or N-methyl-D-aspartate (NMDA) (路) on ACTH secretion in catheterized fetal sheep between days[110][111][112][113][114][115] (N = 5) [120][121][122][123][124][125]. (N = 5) and[135][136][137][138][139][140] (N = 8).…”
mentioning
confidence: 99%